Islamic Legal View on Buying and Selling Bitcoin - Hasan, Zulfikar; Bobby Syuhada; Nur Indira (Jurnal Ekonomi KIAT, 2023)
The term "cryptocurrency" refers to a form of digital or virtual currency that does not exist in tangible form like paper money. That cryptocurrency can only be used with internet-connected PCs, laptops, smartphones, and other devices. Cryptosystems that make use of the blockchain system have a number of advantages, including the speed, convenience, and security of transactions, as well as the ability to be used in all nations and continents. However, there is still room for improvement in the circulating cryptocurrency, including the absence of supervisory authorities. Experts, including Islamic scholars, are constantly debating the advantages and disadvantages of using cryptocurrencies. The Koran, al-Hadith, Qiyas, and Sad-Adzariyah are the sources used in this study to examine the dynamics of cryptocurrency use from the perspective of ushul fiqh. Increasingly, cryptocurrency transactions are used for speculation, which violates Islamic principles. According to Surah Al-Qur'an An-Nisa verse 29, the elements of superiority are gharar and maysir, so the use of cryptocurrencies is permitted subject to certain conditions. Additionally, a country's legality must be clear for cryptocurrency to be used safely.